Tris inhibits a GH1 β-glucosidase by a linear mixed inhibition mechanism - Rafael S. Chagas; Sandro R. Marana (PLoS ONE, 2025)
Here we demonstrate that Tris (2-amino-2-(hydroxymethyl)-1,3-propanediol), largely used as a buffering agent, is a linear mixed inhibitor ( K i =  12 ±  2 mM and α =  3 ±  1) of the GH1 β-glucosidase from the insect Spodoptera frugiperda (Sfβgly). Such an inhibition mechanism implies the formation of a non-productive ESI complex involving Sfβgly, substrate, and Tris. In addition, Tris binding reduces by 3 fold the enzyme affinity for the substrate. Hence, at concentrations higher than the K i , Tris can completely abolish Sfβgly activity, whereas even at lower concentrations the presence of Tris causes underestimation of β-glucosidase kinetic parameters ( K m and k cat ). In agreement with the inhibition mechanism, computational docking showed that Tris could bind to a pocket placed at the lateral of the active site opening in the Sfβgly-substrate complex, hence leading to the formation of an ESI complex. In agreement with the crystallographic data available, computational docking also showed that Tris may find binding spots in the interior of the active site of the Sfβgly and several GH1 β-glucosidases. Moreover, the variety of their active site shapes results in a multiplicity of binding profiles, foreseeing different inhibition mechanisms. Thus, Tris inhibition may affect other GH1 β-glucosidases. This remark should be taken into account in their study, highlighting the importance of the appropriate buffer for accurate enzyme characterization.